Five-year outcome and predictors of success after second-generation cryoballoon ablation for treatment of symptomatic atrial fibrillation. (1st September 2018) - Akkaya, Ersan; Berkowitsch, Alexander; Zaltsberg, Sergej; Greiss, Harald; Hamm, Christian W.; Sperzel, Johannes; Kuniss, Malte; Neumann, Thomas
Abstract: Introduction: Data on long-term outcomes of cryoballoon ablation for treatment of atrial fibrillation (AF) are sparse. Here, we report the first 5-year follow-up results and predictors of outcome for pulmonary vein isolation (PVI) using the second-generation cryoballoon (CB-Adv) in patients with symptomatic AF. Methods and results: For this prospective observational study, we enrolled 178 patients with paroxysmal (132/178 [74.2%] patients) or persistent AF who underwent PVI with CB-Adv at our institution during 2012. Clinical success was defined as freedom from AF, atrial flutter or atrial tachycardia recurrence >30-s following the 3-month blanking period. Follow-up data were collected during outpatient clinic visits and included Holter-ECG recordings. The impacts of several variables on outcome were evaluated by means of univariate and multivariate analyses and Cox proportional hazards regression models. PVI was sufficient in restoring and maintaining sinus rhythm in 59.0% (n = 105) of patients (paroxysmal AF: 81/132 (61.4%) patients; persistent AF: 24/46 (52.2%) patients, P = 0.20). The median procedure and fluoroscopy times were 126 (interquartile range 114/150) and 20 (16/26) min, respectively. Cox regression analysis showed that left atrial area ≤21 cm 2 and the absence of diabetes independently predicted outcome. Conclusions: Sinus rhythm was maintained in a substantial proportion of patients even 5 years after CB-Adv ablation. Patients with a non-enlarged left atrium without diabetes had the best outcome. Highlights: We present the first reportof 5-year outcome after pulmoary vein isolation using the second-generationcryoballoon. After a single procedure, 59.0% of the patients maintained sinus rhythm during long-term follow-up. Patients with a left atrial area ≤21 cm 2 without diabetes showed the best outcome. Ongoing surveillance is warranted, even if pulmonary vein isolation is deemed initially successful.